UNDERGROUND ECONOMY : TINJAUAN PERSPEKTIF FISKUS DAN WAJIB PAJAK - Asri Lestari; Anggelya Fitri Romadhona; Aldi Supriatna; Rismayanti Nurfitriani; Sefti Sabilla Aziz (Journal of Taxation Analysis and Review, 2021)
The underground economy in Indonesia has now become a factor triggering the loss of state revenue from the tax sector. If these activities are not handled properly, the stability of the state financial system will be poor. Researchers conducted this study aimed to analyze and review the views of taxpayers and tax authorities. By using qualitative methods and descriptive approaches. This study uses primary data in the form of interviews. The data obtained were 5 taxpayers who we visited at their respective homes in Subang Regency. As well as 2 tax officers who work at KPP Pratama Subang. The result of this research is that the underground economy has a positive effect on taxpayers who do not comply with tax regulations. Because they do not need to spend money and time to process tax payments. However, these activities have a negative effect on the state, the consequence will be a loss of tax revenue for the state.